2011
DOI: 10.1002/mus.22161
|View full text |Cite
|
Sign up to set email alerts
|

Full‐length phrenic nerve transfer as the treatment for brachial plexus avulsion injury to restore wrist and finger extension

Abstract: Neurotization of phrenic nerve to the medial portion of the radial nerve at the level of latissimus dorsi insertion is a feasible means of restoring wrist and finger extension in cases of complete brachial plexus avulsion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Many studies have reported that the surgical method is demonstrated to achieve satisfactory clinical results and have no significant effect on the functions of the uninjured side [19][20]. Theoretically, treatment of brachial plexus nerve injury by transferring the C7 from the uninjured side has the following advantages: (1) A number of myelinated nerve fibres make it possible to selectively reconstruct multiple groups of injured nerves and contribute to growth of nerve fibres on the distal end of the affected limb; (2) A very high level of innervation is present between the C7 nerve root and C6 and C8 nerve roots and complete or partial cut of the C7 nerve root has no significant effect on the uninjured side, which is relatively safe; (3) The probability of separate injury of the C7 nerve root (middle trunk) is very low in primary traumas [21][22][23]. However, the disadvantageous factors of the surgical method should not be ignored.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported that the surgical method is demonstrated to achieve satisfactory clinical results and have no significant effect on the functions of the uninjured side [19][20]. Theoretically, treatment of brachial plexus nerve injury by transferring the C7 from the uninjured side has the following advantages: (1) A number of myelinated nerve fibres make it possible to selectively reconstruct multiple groups of injured nerves and contribute to growth of nerve fibres on the distal end of the affected limb; (2) A very high level of innervation is present between the C7 nerve root and C6 and C8 nerve roots and complete or partial cut of the C7 nerve root has no significant effect on the uninjured side, which is relatively safe; (3) The probability of separate injury of the C7 nerve root (middle trunk) is very low in primary traumas [21][22][23]. However, the disadvantageous factors of the surgical method should not be ignored.…”
Section: Discussionmentioning
confidence: 99%